Enzyme immobilization on carbon nanomaterials: Loading density investigation and zeta potential analysis - Min, Kyoungseon; Kim, Jungbae; Park, Kyungmoon; Yoo, Young Je (ELSEVIER SCIENCE BV, 2012)
Although enzymes are attractive catalysts due to their own specificity, industrial applications have been hampered because of their cost, reusability, and easy deactivation under conditions far from their optimum. Immobilization has been the most popular and successful approach to overcome these limitations and enable enzymes to be used in large scale industrial processes. Recent progress in nanotechnology leads research interests toward the immobilized enzyme on/into nanoscale support material. In this study, carbon nanopowder and single-walled carbon nanotube (SWNT) were selected as the immobilization support and non-covalent functionalization method was developed using 1-pyrene butyric acid in order to retain the unique properties of the carbon nanomaterial. Tyrosinase, glucose oxidase, and lipase B were immobilized on the support and showed high loading densities; 2.09 mg tyrosinase, 0.626 mg lipase B, and 2.50 mg glucose oxidase per mg support, respectively. The isotherm curve fitted for Langmuir model indicated that high loading densities were based on the monolayer coverage of full surface, not multi-layer aggregation. We attempted zeta-potential analysis for determining the influential factor affecting the loading density and consequently it was validated that the electrostatic interaction between the enzyme and the support is the critical factor on the high loading density in not only simple adsorption but also in covalent immobilization. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: GLUCOSE-OXIDASE; PROTEIN IMMOBILIZATION; L-DOPA; NANOTUBES; FUNCTIONALIZATION; NANOPARTICLES; TYROSINASE; PARTICLES; STABILITY; COMPOSITE